Antioxidant potential of commonly consumed underutilized leguminous vegetables. Issue 4 (4th July 2019) - Koley, Tanmay Kumar; Maurya, Arti; Tripathi, Ajay; Singh, B. K.; Singh, Mamta; Bhutia, T. L.; Tripathi, P. C.; Singh, Bijendra
ABSTRACT: Underutilized, or lesser-known legumes, adapted to local conditions, could be a good source of nutrients, but have not received sufficient examination. Of particular interest is amounts of antioxidants in underutilized legumes. The underutilized legumes winged bean [ Psophocarpus tetragonolobus (L.)], sword bean [ Canavalia gladiata (Jacq.) DC.], jack bean [ C. ensiformis (L.) DC.], scarlet bean ( Phaseolus coccineus L.), and velvet bean [ Mucuna pruriens (L.) DC], were evaluated for phenolics content and antioxidant potential. For comparison, the commercially cultivated legumes vegetable such as French bean ( Phaseolus vulgaris L.), green and purple, cowpea [ Vigna unguiculate (L.) Walp.], garden pea ( Pisum sativum L.), edible-podded pea ( Pisum sativum var. macrocarpon L.), and fenugreek ( Trigonella foenum-graecum L.) were also evaluated for phenolics content and antioxidant potential. Antioxidant activity was measured using the in vitro assays: ferric reducing antioxidant power (FRAP), cupric reducing antioxidant power (CUPRAC), 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and Trolox equivalent antioxidant capacity assays (TEAC). Total phenols and total flavonoids varied from 18.38 to 595.50 mg/100 g fresh weight (fw) and 4.24–154.58 mg/100 g fw, respectively. Velvet bean seed and pods were the richest sources of phenolic antioxidants with very strong potential. A high, positive, correlation exists between phenolics and antioxidant potentials indicating phenolics are the principal natural antioxidants present in the legumes. Agglomerative hierarchical clustering was used to understand possible classification of legume vegetables based on their bioactive antioxidant compounds and antioxidant potential. The distance between velvet bean seed and pods was less pronounced than the distance between them and the other samples indicating they have greater antioxidant potential than the other legumes. Use of velvet bean in the diet could increase intake of health-promoting compounds.